The saga of dyssynchrony imaging: Are we getting to the point - Galli, Elena; Galand, Vincent; Le Rolle, Virginie; Taconne, Marion; Wazzan, Adrien Al; Hernandez, Alfredo; Leclercq, Christophe; Donal, Erwan (Frontiers in Cardiovascular Medicine, 2023)
Cardiac resynchronisation therapy (CRT) has an established role in the management of patients with heart failure, reduced left ventricular ejection fraction (LVEF<35%) and widened QRS (> 130 msec). Despite the complex pathophysiology of left ventricular (LV) dyssynchrony and the increasing evidence supporting the identification of specific electromechanical substrates that are associated with a higher probability of CRT response, the assessment of LVEF is the only imaging-derived parameter used for the selection of CRT candidates. This review aims to 1) provide an overview of the evolution of cardiac imaging for the assessment of LV dyssynchrony and its role in the selection of patients undergoing CRT; 2) highlight the main pitfalls and advantages of the application of cardiac imaging for the assessment of LV dyssynchrony. 3) provide some perspective for clinical application and future research in this field. Conclusion: the road for a more individualized approach to resynchronization therapy delivery is open and imaging might provide important input beyond the assessment of LVEF.